Dual layer composite nanofiltration hollow fiber membranes for low-pressure water softening - Setiawan, Laurentia (2014)
Nanofiltration (NF) membrane process has become increasingly attractive due to their unique characteristics to selectively remove specific compounds or ions. The most commonly NF membranes are negatively charged which is unsuitable for hardness removal. Therefore, the development of novel NF membranes with a positively charged skin has become a key issue for low pressure water softening. In this study, dual layer microporous hollow fiber membranes were fabricated using Torlon poly(amide-imide) (PAI) as the material of the selective outer layer and polyethersulfone (PES) as the material of the porous support inner layer. A positively charged NF-like selective layer was developed by a simple polyelectrolyte cross-linking using polyallylamine (PAAm). The newly developed (PAI-PAAm)-PES dual layer hollow fiber membranes show a salt water permeability of 15.8 L/m2.h.bar and high Mg2+ and Ca2+ rejections of 94.2% and 92.3%, respectively, at operating pressure of 2 bar using a 3000 ppm TDS feed solution. This study provides a simple and effective approach to produce positively charged NF hollow fiber membranes for water softening applications with low energy consumption.